Pemakaian Kaedah Fiqh Terhadap Isu Penyerupaan (Al-Tasyabbuh) dalam Konteks Masyarakat Majmuk di Malaysia - Ramli, Mohd Anuar; Hj Ismail, Paizah; Abdullah, Ahmad Badri (Jurnal Fiqh, 2014)
his research focuses on some Islamic legal maxims (al-Qawa’id al-Fiqhiyyah) pertaining to the issue of prohibited imitation (al-tasyabbuh) among Muslims of non-Muslims. Several issues that relate to the interaction process between Muslim and non-Muslim societies in the contemporary local context are discussed in this paper, such as issues concerning costumes, celebrations, and politics. In the process, in analysing these issues, the Islamic legal maxims are being applied, which are formulas concluded by fiqh scholars by referring to Qur’anic texts and prophetic traditions, as well as the jurisprudential conclusions from classical works that discussed al-tasyabbuh intensively. The results from the research showed that these maxims are able to become general rules for classifying any act of interaction between Muslims and non-Muslims as a practice of prohibited imitation (al-tasyabbuh).